Topical Tacrolimus in Vitiligo: Consensus Paper from the Pigmentary Disorders Society - Sarkar R; Dogra S; Vinay K; Sinha S; Narayan VR; Kumaran MS; Podder I; Jagadeesan S; Bhalla M; Das A; Lakhani R; Sharma R; et al. (Clinical, Cosmetic and Investigational Dermatology)
Rashmi Sarkar,1 Sunil Dogra,2 Keshavamurthy Vinay,2 Surabhi Sinha,3 Vignesh R Narayan,4 Muthu Sendhil Kumaran,2 Indrashis Podder,5 Soumya Jagadeesan,6 Mala Bhalla,7 Anupam Das,8 Ridhima Lakhani,9 Richa Sharma,10 Shyamanta Barua,11 Vijay K Somani,12 D M Thappa,13 Venkataram Mysore,14 Bhavesh Swarnkar15 1Department of Dermatology, Lady Hardinge Medical College and Associated KSCH and SSK Hospital, New Delhi, India; 2Department of Dermatology Venereology & Leprology, Postgraduate Institute of Medical Education & Research (PGIMER), Chandigarh, India; 3Department of Dermatology, Lady Hardinge Medical College and Associated Hospitals, New Delhi, India; 4Department of Dermatology Venereology and Leprology, MS Ramaiah Medical College, Bangalore, Karnataka, India; 5Department of Dermatology, CMSDH, Kolkata, West Bengal, India; 6Department of Dermatology, Amrita Institute of Medical Sciences, Kochi, Kerala, India; 7Department of Dermatology, Government Medical College and Hospital, Chandigarh, India; 8Department of Dermatology, KPC Medical College and Hospital, Kolkata, West Bengal, India; 9Consultant Dermatologist, Department of Dermatology, Fortis Hospitals, Shalimar Bagh, New Delhi, India; 10Consultant Dermatologist, Twacha Skin Clinic, New Delhi, India; 11Department of Dermatology, Assam Medical College & Hospital, Dibrugarh, Assam, India; 12Consultant Dermatologist, Dermatrendz, Hyderabad, Telangana, India; 13Department of Dermatology and STD, JIPMER, Puducherry, India; 14Consultant Dermatologist Venkat Center for Skin ENT and Plastic Surgery, Bengaluru, Karnataka, India; 15Consultant Dermatologist, Indore, Madhya Pradesh, IndiaCorrespondence: Rashmi Sarkar, Department of Dermatology, Lady Hardinge Medical College and Associated KSCH and SSK Hospital, New Delhi, India, Tel +91 9818244340, Email rashmisarkar@gmail.comBackground: Tacrolimus, a topical calcineurin inhibitor (TCI) with immunomodulatory effects, is considered a viable treatment option for vitiligo. A consensus building exercise was undertaken to determine the role and clinical utility of topical tacrolimus in the management of vitiligo using input from experts in the field of dermatology.Methods: Seventeen experts collaborated to create consensus statements using a modified Delphi methodology. A questionnaire on effectiveness, safety and utility of topical tacrolimus in different types of vitiligo, duration, frequency, monotherapy and combination and other aspects was shared, and a concordance rate of 75% was preset to have consensus. A physical meeting was conducted to discuss statements, which did not achieve consensus.Results: Amongst 34 statements derived from round one, consensus was not achieved for 9 statements. In the second round, consensus was achieved for 2/9 statements, hence in the physical meeting, discussion was done to reframe the remaining seven statements. Apart from these 34 statements, questions pertaining to “Vitiligo: types and presentation in clinical practice”, where consensus was not intended, are presented as descriptive statements.Conclusion: Topical tacrolimus ointment has a favorable risk benefit profile to be used as one of the first-line agents for vitiligo. Combination of topical tacrolimus and narrow band Ultraviolet-B (NBUVB) was recommended as an effective treatment for non-segmental vitiligo. Recommended frequency of application was once or twice daily for optimal results. Apart from a transient burning sensation, topical tacrolimus has a favorable safety profile.Keywords: topical calcineurin inhibitor, immunomodulatory, non-segmental vitiligo, depigmenting, autoimmune, autoreactive T cells, tacrolimus